Efektivitas Penerapan Undang-Undang Nomor 23 Tahun 2004 tentang KDRT di Sumatera Barat - Trisna, Trisna Latifah Nur; Andri Muda Nst (Islamic Circle, 2024)
Domestic violence (DV) in Sumatera Barat is a serious issue that requires special attention from a legal perspective. Law No. 23 of 2004 concerning the Elimination of Domestic Violence is expected to be an effective instrument in providing protection for victims, especially women and children. This study aims to assess the effectiveness of the implementation of this law in providing legal protection for DV victims. Although the regulation has been implemented, the increasing number of domestic violence cases that are not optimally addressed indicates that there are problems in its execution. The method used in this research is a juridical analysis that focuses on examining the legal norms contained in Law No. 23 of 2004. Data were collected through the study of legal documents, including relevant implementing regulations. The findings show that challenges in the implementation of this law, such as a lack of understanding among law enforcement and low community awareness of victims' rights, still dominate. For instance, in several regions, reported DV cases are often not adequately followed up, particularly due to limitations in supporting infrastructure, such as inadequate integrated service centers to assist in the recovery of victims.